Bottom-up Budgeting Process Assessment: Agusan del Norte - Danileen Kristel C. Parel; Keith C. Detros; Christine Ma. Grace R. Salinas (Philippine Institute for Development Studies (PIDS), 2015)
The Aquino administration through the Human Development and Poverty Reduction Cluster (HDPRC) and Good Governance and Anti-Corruption Cluster (GGACC) launched the bottom-up budgeting (BUB) exercise in 2012. The strategy hopes to empower civil society organizations (CSOs) and citizens' groups to engage local government and national government agencies and make them more responsive to people's needs. The program is desirable not only because of the additional funds it provides, but because it promotes transparency in governance. Furthermore, the BUB not only improves CSO-LGU relations, but also gives CSOs a sense of empowerment and heightens their political efficacy. Since the first round, the BUB process has improved significantly in terms of the level of CSO participation, clarity of guidelines, and the process as a whole. It has made planning and budgeting more inclusive and reflective of the local needs from the grassroots level. Despite these improvements, some issues and concerns still need to be addressed in terms of CSO engagement, process facilitation, social preparation, project identification and prioritization, subproject implementation, and service delivery. This paper assesses the FY 2015 planning process as well as the FY 2013 subproject implementation in three municipalities in Agusan del Norte, and explores areas for further improvement in the implementation of the subsequent rounds of the BUB.
Keywords: 330; Philippines; local governance; grassroots; participatory planning; bottom-up budgeting (BUB); poverty alleviation; budget reform; Agusan del Norte; Butuan City; Buenavista; Las Nieves; civil society organizations (CSOs)